The Urgency of The Exemplary Story of Rasulullah PBUH in Children Aged 6-7 Years (The Perspective of Kuttab Alfatih Cibinong Teachers) - Anisa Nurul Zahra; Lara Fridani; Iva Sarifah (International Conferences on Early Childhood Education Proceedings, 2023)
Rasulullah (peace be upon him) is a role model for all Muslims. Learning the example of Rasulullah in early childhood can be one of the facilities in developing the child. This is because early childhood is the golden age of children in developing. Thus, this study aims to explain the urgency of learning the example of Rasulullah in children aged 6-7 years according to the views of teachers at Kuttab Alfatih. Kuttab Alfatih is a school that has a curriculum that refers to the Al-Quran, Sunnah, and books of scholars that discuss generation education. In learning activities, children are facilitated with exemplary stories, one is the story of Rasulullah. This research was conducted through a case study method using interview and observation data collection techniques. The data sources in this study are two sirah teachers at Kuttab Alfatih Cibinong. The results of this study conclude that learning the exemplary story of Rasulullah is very important to be facilitated in children aged 6-7 years, because this period is the child's transition to a new level of development. At this time, children need stimulus, guidance, as well as role models and examples. Nowadays, role models for children have become ambiguous and inappropriate. Nowadays, children look up to fictional characters as their role models. In addition, at this age children are able to receive new information and apply it to their daily lives. If the character used as a role model for children is not ethically and morally good, children can apply the same thing to their daily lives. That way, the example of Rasulullah can become new knowledge and a model for children, so that it can be applied in children's lives